Censorship detected in AZ (Azerbaijan) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Azerbaijan. Data sourced from OONI.
Censorship Incident ID: AZ-2026-1533. Severity: critical. Confidence: 90%